Manufacturing apps and the Dynamic House of Quality: Towards an industrial revolution. (August 2017) - Chen, Aoyu; Dinar, Mahmoud; Gruenewald, Thomas; Wang, Max; Rosca, Justinian; Kurfess, Thomas R.
Abstract: Modern manufacturing is becoming more powerful and flexible due to the decreasing cost of smart sensors and data processing platforms. Modularized functions related to machine tool condition monitoring, signal processing and adaptive control can be packaged into standalone manufacturing apps for a better understanding of machine operations. Based on the Service Oriented Architecture (SOA), manufacturing apps can be structured to work either independently or as a group for performing more complicated tasks. The Dynamic House of Quality (HoQ) provides a platform that companies, app users and app writers can benefit from in understanding what apps customers need the most, and what apps are more likely to be bundled in app groups. Potential applications of the Dynamic HoQ for manufacturing apps are discussed in this paper.